Formulation, Characterization and Pharmacokinetics of Long-acting Ceftiofur Hydrochloride Suspension - Xie, Shuyu; Zhang, Xiaoqiu; Luo, Wanhe; Meng, Kuiyu; Chen, Dongmei; Pan, Yuanhu; Tao, Yanfei; Huang, Lingli; Liu, Zhenli; Wang, Yulian; Yuan, Zonghui (Current Drug Delivery, 2021)
Objective: A ceftiofur hydrochloride long-acting oily suspension with no irritation was prepared by testing and optimizing the types and amounts of organic solvents, suspending agents, and surfactants. Methods: Its properties, stability, injection site irritation, in vitro release, and pharmacokinetics in pigs were evaluated. The optimum formulation was used ethyl oleate, aluminum monosterate, and span-80 as organic solvents, suspending agents, and surfactant, respectively. The drug microparticles were uniform long strip with size of 1.53 ± 0.11 μm and no agglomerations, and were evenly dispersed. The re-dispersed time, sedimentation rate and pH value of the suspension were 4 s under a magnetic shaker rotating at 20 r/min, 1 and 5.0, respectively. It could go through 7-gage needle smoothly with withdrawal volume of 9.9 mL/min. Results: The suspension showed good stability when stored away from light, no irritation at the injection site and sustained release in PBS buffer. After intramuscular administration, the drug concentration above 0.15 μg/mL was last for 120 h. Its elimination half-life (T1/2ke), mean residence time (MRT), and bioavailability were increased by 1.73, 1.62, and 2.16 times compared to Excenel®. Conclusion: The results suggested that the suspension had excellent sustained-release and will make ceftiofur hydrochloride more effective and convenient to use.
Keywords: oily suspension